Seasonal variation of vitamin and sterol content of chironomidae larvae - Kara, Tuba (My University, 2013)
In the present study, seasonal variation of vitamin and sterol content of Chironomidae larvae were determined by using HPLC. As the result of vitamin analysis, we found ?-tocopherol, retinol, Kb K2, D2 andD3. When the seasonal variation of vitamin groups were compared, a significant increase was observed in vitamin Kb K2, D2 and ?-tocopherol in all seasons. A significant increase was observed in vitamin D3 in spring. And also vitamin A level high in autumn and winter, ?-tocopherol level was significantly high among vitamins. When vitamin groups were compared statistically, differences were detected between seasons (p<0.001). Analyzing the content of sterol, we found ergosterol, cholesterol, stigmasterol and ?-sitosterol in all seasons. Cholesterol level was found to be significantly high in sterols. When sterol contents were compared statistically, differences were detected between seasons (p<0.001). In conclusion, the reasons for these differences are larval development feature and the variety of food in different seasons. © 2013 Asian Network for Scientific Information.
Keywords: Chironomidae; Diptera; Seasonal variation; Sterol; Vitamin